Green IoT: Current Scenario & Future Prospects - Bansal, Malti; Kumar, Aayush; Virmani, Aman (Journal of Trends in Computer Science and Smart Technology, 2021)
Demands of world's whole population for insubstantial products has thus prompted the need of effective utilization of materials and assets. As huge changes in society have been impacted for good by the advancement in Information and Communication Technology, their use has a negative effect on the environment and human wellbeing. The reason being, our society is in a deep need of a greener future where there is judicial use of resources along with minimal use of non-renewable resources. This will eventually decrease the pollution & promote lesser power consumption. Green Internet of Things takes one of the main parts while in transit to make a sustainable & green spot for living. We investigate and talk about how the different empowering advancements, (for example, the Internet, smart objects, sensors, and so forth) can be effectively implemented to accomplish a green IoT. Moreover, we likewise audit different IoT applications, standardization and projects which are at present under way. At last, we recognize a portion of the challenges which should be tended to later on to empower a green IoT.